ANALISIS KEBANGKRUTAN PERUSAHAAN DENGAN METODE Z-SCORE ALTMAN PADA 10 (SEPULUH) PERUSAHAAN PROPERTY DAN REAL ESTATE YANG TERDAFTAR DI BEI - Oktavian, Ricky Eltin; Sandari, Tries Ellia (JEA17: Jurnal Ekonomi Akuntansi, 2018)
ABSTRACTThe Purpose of this research is find out, analyze, and predict bankcrupcy potency of  property dan real estate company listed on the Indonesia Stock Exchange. Method Z-Score Altman uses five financial ratios that is Working Capital to Total Assets (X1), Retained Earnings to Total Assets (X2), Earnings Before Interest and Taxes to Total Assets (X3), Book Value of Equity to Book Value of Total Debt (X4), and Sales to Total Assets (X5). The results of the Altman Z-Score method that classify companies in three categories which are not bankrupt (safe zone), vulnerable to bankruptcy (gray zone) and bankruptcy (distress zone). Key Word: Capital, Retained Earnings, Earnings Before Interest, Taxes, Total Assets